Framing advance care planning in Parkinson disease: Patient and care partner perspectives. (28th May 2019) - Lum, Hillary D.; Jordan, Sarah R.; Brungardt, Adreanne; Ayele, Roman; Katz, Maya; Miyasaki, Janis M.; Hall, Anne; Jones, Jacqueline; Kluger, Benzi
Abstract : Objective: Advance care planning (ACP) is a core quality measure in caring for individuals with Parkinson disease (PD) and there are no best practice standards for how to incorporate ACP into PD care. This study describes patient and care partner perspectives on ACP to inform a patient- and care partner-centered framework for clinical care. Methods: This is a qualitative descriptive study of 30 patients with PD and 30 care partners within a multisite, randomized clinical trial of neuropalliative care compared to standard care. Participants were individually interviewed about perspectives on ACP, including prior and current experiences, barriers to ACP, and suggestions for integration into care. Interviews were analyzed using theme analysis to identify key themes. Results: Four themes illustrate how patients and care partners perceive ACP as part of clinical care: (1) personal definitions of ACP vary in the context of PD; (2) patient, relationship, and health care system barriers exist to engaging in ACP; (3) care partners play an active role in ACP; (4) a palliative care approach positively influences ACP. Taken together, the themes support clinician initiation of ACP discussions and interdisciplinary approaches to help patients and care partners overcome barriers to ACP. Conclusions: ACP in PD may be influenced by patient and care partner perceptions and misperceptions, symptoms of PD (e.g., apathy, cognitive dysfunction, disease severity), and models of clinical care. Optimal engagement of patients with PD and care partners in ACP should proactively address misperceptions of ACP and utilize clinic teams and workflow routines to incorporate ACP into regular care.